NUTRITIONAL INTERVENTION TRIALS MODEL IN POOR AREAS OF BALI PROVINCE - Kadek Tresna Adhi; Ni Wayan Arya Utami; I Made Suka Adnyana (Institute for Research and Community Services Udayana University, 2017)
Abstract The result from food utilization analysis in 2015 showed that a needed for a community based nutrition intervention model to decrease malnutrition cases among under five years children. This was non experimental study using pre-post test approached, conducted in Karangasem and Bangli regency. Samples were selected by purposive sampling method. Data were collected by questionnaire and observation. Nutrition intervention model was arranged in the form of training module given to society’s figure and integrated post service’s cadres. Result from trial of training module I showed no significant difference between means of knowledge before and after training with p-value (1,00) > ? (0,05), meanwhile in the trial of training module II showed significant difference between means of knowledge before and after training with p-value (0,048) < ? (0,05). Needed a model for socialization the nutrition intervention’s module which actively involved society’s figures and integrated post service’s cadre and ad vocation to policy maker thereby it can support the success of community nutrition improving program.